2020
DOI: 10.5194/hess-24-6075-2020
|View full text |Cite
|
Sign up to set email alerts
|

Key challenges facing the application of the conductivity mass balance method: a case study of the Mississippi River basin

Abstract: Abstract. The conductivity mass balance (CMB) method has a long history of application to baseflow separation studies. The CMB method uses site-specific and widely available discharge and specific conductance data. However, certain aspects of the method remain unstandardized, including the determination of the applicability of this method for a specific area, minimum data requirements for baseflow separation and the most accurate parameter calculation method. This study collected and analyzed stream discharge … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Studies have found that the effectiveness of using tracers in baseflow separation depends on the correlation between SEC and streamflow rate of the catchment system. Catchments with a higher magnitude of the correlation are more likely to have better performance (Guo et al., 2022; Lyu et al., 2020; Tunqui Neira, Tallec, et al., 2020). Therefore, this study applies a Spearman Correlation Coefficient (SCC) of −0.3 as the threshold to filter the catchments following Lyu et al.…”
Section: Study Catchments and Water Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have found that the effectiveness of using tracers in baseflow separation depends on the correlation between SEC and streamflow rate of the catchment system. Catchments with a higher magnitude of the correlation are more likely to have better performance (Guo et al., 2022; Lyu et al., 2020; Tunqui Neira, Tallec, et al., 2020). Therefore, this study applies a Spearman Correlation Coefficient (SCC) of −0.3 as the threshold to filter the catchments following Lyu et al.…”
Section: Study Catchments and Water Datamentioning
confidence: 99%
“…Therefore, this study applies a Spearman Correlation Coefficient (SCC) of −0.3 as the threshold to filter the catchments following Lyu et al. (2020). For turbidity a threshold of 0.3 is used as it is positively correlated with streamflow (Tilahun et al., 2013; Zarnaghsh & Husic, 2021).…”
Section: Study Catchments and Water Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This might introduce uncertainties in the monthly analysis. However, we adopted two methods in assessing annual (3) In this study, although baseflow was separated using the combined baseflow separation method with high accuracy at the annual time scale, there were biased estimations for seasonal baseflow (Lyu et al, 2020;Zhang et al, 2013).…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%